A Contemporary Socio-Legal Evaluation of Indonesia's Post-Reformation Child Marriage Policies - Asep Saepullah; Abdul Aziz; Ipuk Widayanti; M. Zidny Nafi’ Hasbi; Adamu Abubakar Muhammad (Faculty of Sharia, IAIN Metro, 2025)
This study examines the regulation of child marriage in post-reform Indonesia through a socio-legal approach that integrates the principles of maqāṣid al-sharīʿah. Although recent reforms have raised the minimum age for marriage, existing policies remain inadequate to address fundamental challenges such as gender inequality, educational disparities, and public health risks. Using a doctrinal legal method complemented by content analysis, this research analyses statutory texts, academic literature, and policy documents within a qualitative interpretive paradigm informed by social jurisprudence in its socio-religious context. The findings reveal that child marriage persists due to deeply rooted structural issues, including poverty and gender inequality, which are reinforced by socio-religious norms surrounding marriage, sexuality, and morality. Regulatory inconsistencies and divergences among institutional actors further exacerbate the problem, disproportionately affecting girls. The study argues that efforts to eliminate child marriage require policies aligned with a maqāṣid al-sharīʿah framework that addresses structural root causes and fosters a gender-just transformation of society. In terms of academic contribution, this research bridges Islamic legal theory with contemporary socio-legal challenges, demonstrating how maqāṣid al-sharīʿah can inform progressive policy reform. It contributes to the literature by providing a framework for integrating normative Islamic values with socio-legal interventions, highlighting the interplay between law, culture, and religion in shaping social outcomes. Methodologically, it advances the combination of doctrinal and content analysis within a qualitative interpretive approach, offering a model applicable to other socio-legal issues in Muslim-majority contexts. The study concludes with normative recommendations for reforming child marriage policies in accordance with Islamic legal principles, prioritising the protection, dignity, and rights of children and women while promoting gender equality and long-term societal well-being.